On the genus Cebrennus Simon, 1880 in Iran with description of a new species from Iranian Central Desert (Araneae: Sparassidae) - Moradmand, Majid; Zamani, Alireza; Jäger, Peter (Zootaxa, 2016)
The taxonomic knowledge on the desert-dwelling sparassid genus Cebrennus Simon, 1880 in Iran is updated by describing a new species, Cebrennus rambodjavani sp. nov. (male) from northern Qom in Iran’s Central Desert, and reviewing the material of the previous Iranian record of the genus [sub C. kochi (O. Pickard-Cambridge, 1872)] from Bushehr, southern Iran, which is found to be a misidentification. A revised definition of the term “embolus kink”, a male copulatory structure in Cebrennus, is given. A comparative discussion of this structure between several representatives of the genus Cebrennus is included.